2005
DOI: 10.1128/mcb.25.17.7473-7483.2005
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-Repressing Factor Inhibits Elongation of Human Immunodeficiency Virus Type 1 Transcription by DRB Sensitivity-Inducing Factor

Abstract: Human immunodeficiency virus type 1 (HIV-1) is able to establish a latent infection during which the integrated provirus remains transcriptionally silent. In response to specific stimuli, the HIV-1 long terminal repeat (LTR) is highly activated, enhancing both transcriptional initiation and elongation. Here, we have identified a specific binding sequence of the nuclear NF-B-repressing factor (NRF) within the HIV-1 LTR. The aim of this work was to define the role of NRF in regulating the LTR. Our data show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…In agreement with this, we found that p65 and NRF were both recruited to the IL-8/CXCL8 promoter in hASM cells following NE stimulation. This NRF-NF-B protein-protein interaction has been suggested to prevent recruitment of elongation factor DRB sensitivity-inducing factor and hence to interrupt the transcriptional elongation for the HIV-1 LTR reporter (26). However, such an observation was made on a synthesized promoter, where the condition of nucleosome assembled may be different from that at the native promoters or the DNA may be naked, therefore effects via the chromatin would be ignored.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In agreement with this, we found that p65 and NRF were both recruited to the IL-8/CXCL8 promoter in hASM cells following NE stimulation. This NRF-NF-B protein-protein interaction has been suggested to prevent recruitment of elongation factor DRB sensitivity-inducing factor and hence to interrupt the transcriptional elongation for the HIV-1 LTR reporter (26). However, such an observation was made on a synthesized promoter, where the condition of nucleosome assembled may be different from that at the native promoters or the DNA may be naked, therefore effects via the chromatin would be ignored.…”
Section: Discussionmentioning
confidence: 98%
“…Studies using a HIV-1 LTR reporter showed that NRF was constitutively binding to LTR and inhibiting its transcription activity. However, NRF seems to become required for transcriptional activation of the HIV-1 LTR upon stimulation with PMA and ionomycin (26), in which the level of NRF binding to the LTR is not changed. It is therefore suggested that endogenous NRF plays a dual role in gene transcription (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NKRF is known to bind specific DNA sequences in several NF-κB-regulated genes and to interact with NF-κB/p65, differentially controlling NF-κB-driven transcription under basal and/or stimulated conditions (10)(11)(12)(13)(14). Therefore, proteotoxic stress-induced NKRF expression and dynamic nucleolar-nuclear movement may contribute to NF-κB-driven transcription regulation, with important implications in inflammation and cancer.…”
Section: Resultsmentioning
confidence: 99%
“…8A, the newly raised anti-AP-4 antibody could specifically precipitate AP-4. Although the nature and/or the extent of chromatin formation on transiently transfected DNA templates likely differ from that of chromosomal genes, previous reports of ChIP assays using plasmids containing HIV-1 LTR have validated ChIP studies in transiently transfected cells (32)(33)(34)(35). In Fig.…”
Section: Effect Of the Location Of Ap-4 Site Within Hiv-1 Ltr On The mentioning
confidence: 99%